Three-dimensional static shape control analysis of composite plates using distributed piezoelectric actuators - Shaik Dawood, Mohd. Sultan Ibrahim; Iannucci, Lorenzo; Greenhalgh, Emile S. (Institute of Physics Publishing, 2008)
In this work, based on a linear piezoelectric constitutive model, a three-dimensional finite element code using an eight-node brick element that includes the anisotropic and coupled field effects of piezoelectric actuators has been developed for the static shape control analysis of fibre reinforced composite laminates. The code was used to study voltage sensing and actuation capabilities of piezoelectric actuators on composite laminates. The required input voltages to the actuators in order to achieve a specified structural shape were determined using a weighted shape control method. The code was validated using two test cases obtained from the literature. The results were found to show good correlation for voltage actuation. However, since determining input voltages to achieve the desired structural shape is a type of inverse problem, there are no explicit solutions and hence the results obtained from the present model were not similar to those reported in the literature. The second validation also suggests that the anisotropic and coupled field effects of the piezoelectric actuators cannot be neglected as this has been shown to underestimate the required control voltages. The effects of different lamination angles, boundary conditions, plate length-to-thickness ratios and actuator dimensions on the control voltages have also been reported.